2005
DOI: 10.1186/1472-6815-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds for perception of direction of linear acceleration as a possible evaluation of the otolith function

Abstract: Background: Previous attempts to measure otolith function using ocular counter-rolling have shown poor sensitivity and specificity, thereby hindering a useful clinical application. We have conducted a study to investigate whether thresholds for the perception of the direction of linear acceleration might be an alternative for the clinical evaluation of otolith or statolith function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 10 publications
5
62
2
1
Order By: Relevance
“…However, these studies have not provided two important details: possible effects of aging and possible directional asymmetries. Prior work in the field has focused on a young population that almost never included subjects beyond the age of 40, even though it has been shown that age does effect perception of steady-state translation (Kingma 2005). Because the prevalence of vestibular disorders is much higher after the age of 50 (Agrawal et al 2009), there is a need for normative data in older individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these studies have not provided two important details: possible effects of aging and possible directional asymmetries. Prior work in the field has focused on a young population that almost never included subjects beyond the age of 40, even though it has been shown that age does effect perception of steady-state translation (Kingma 2005). Because the prevalence of vestibular disorders is much higher after the age of 50 (Agrawal et al 2009), there is a need for normative data in older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In comparing cervical (cVEMP) and ocular (oVEMP) results between subjects in their twenties and those older than 50, the amplitude of both responses was decreased by half in the older group. Perception of sinusoids in surge has been shown to decline with age, but no effect of age was seen with lateral motion (Kingma 2005). These prior axis dependent effects have been difficult to interpret because the thresholds found by Kingma et al were significantly lower than those found by others (Benson et al 1986;Gianna et al 1996).…”
Section: The Effect Of Agingmentioning
confidence: 91%
See 1 more Smart Citation
“…1C). For inertial motion, these accelerations far exceed vestibular thresholds (for review, see Gundry, 1978) (Benson et al, 1986;Kingma, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Alternative methods of testing otolith function are being investigated and validated, including assays based on linear motion perceptual thresholds similar to auditory threshold testing (Kingma 2005;MacNeilage et al 2010a;Merfeld 2011;Roditi and Crane 2012;Valko et al 2012). Motion perceptual threshold testing is a promising vestibular testing modality given that the stimuli (head translations or rotations) are physiological and thus test performance may better correlate with symptoms and functional status relative to VEMP testing (Merfeld et al 2010).…”
mentioning
confidence: 99%